2003
DOI: 10.1038/sj.onc.1207055
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of cyclin D3 in TSH-dependent growth of thyrocytes and in hyperproliferative diseases of the thyroid gland

Abstract: We report that cyclin D3 is rate limiting for G1 progression in thyroid follicular cells and that its constitutive upregulation by chronic stimulation of the TSH/cAMP pathway plays a role in human and experimental hyperproliferative diseases of the thyroid gland. These conclusions are supported by in vitro and in vivo studies. In rat thyrocytes (PC Cl 3 cells), cyclin D3 expression is enhanced in response to activation of the TSH/cAMP pathway. Interference with the expression of G1 cyclins (in particular cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Indeed, Pten L/L ;TPO-Cre thyroids were characterized by highly phosphorylated p70S6K1 and S6 proteins, suggesting that PI3K activation is sufficient to stimulate this pathway. We also found that PI3K/Akt activation was associated with increased levels of both cyclin D1 and cyclin D3, consistent with previous data supporting their role in thyrocyte proliferation and human thyroid proliferative disorders (35,36).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, Pten L/L ;TPO-Cre thyroids were characterized by highly phosphorylated p70S6K1 and S6 proteins, suggesting that PI3K activation is sufficient to stimulate this pathway. We also found that PI3K/Akt activation was associated with increased levels of both cyclin D1 and cyclin D3, consistent with previous data supporting their role in thyrocyte proliferation and human thyroid proliferative disorders (35,36).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, in both opposite situations, cAMP differentially regulates the activity and phosphorylation of CDK4 bound to cyclin D1 or to cyclin D3. Cyclin D3 is the predominant D-type cyclin in normal thyrocytes (Depoortere et al, 1998;Van Keymeulen et al, 1999;Motti et al, 2003;Paternot et al, 2006b). Although growth factors mostly activate cyclin D1-CDK4-p21 complexes, cyclin D3-CDK4 is specifically required and activated in the mitogenic stimulation by TSH and cAMP (Depoortere et al, 1998;Motti et al, 2003;Paternot et al, 2006a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D3 is the predominant D-type cyclin in normal thyrocytes (Depoortere et al, 1998;Van Keymeulen et al, 1999;Motti et al, 2003;Paternot et al, 2006b). Although growth factors mostly activate cyclin D1-CDK4-p21 complexes, cyclin D3-CDK4 is specifically required and activated in the mitogenic stimulation by TSH and cAMP (Depoortere et al, 1998;Motti et al, 2003;Paternot et al, 2006a,b). This crucially involves the cAMP-dependent phosphorylation of cyclin D3-bound CDK4 (Paternot et al, 2003Bockstaele et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…19 We previously demonstrated that cyclin D3 expression is rate-limiting for G 1 progression in thyroid follicular cells. 20 Subsequently, we validated cyclin D3 immunostaining in a large series of paraffin-embedded thyroid cancer tissues. 13 Cyclin D3 expression was associated specifically with Hurthle cell carcinoma and had a diffuse and intense nuclear staining pattern.…”
Section: -5mentioning
confidence: 99%